120 Impaired phonemic discrimination in logopenic variant primary progressive aphasia. Issue 6 (27th May 2022) - Johnson, Jeremy; Jiang, Jessica; Benhamou, Elia; Requena-Komuro, Mai-Carmen; lan, Harri Sivasathiasee-; Marshall, Charles; Volkmer, Anna; Rohrer, Jonathan; Warren, Jason; Hardy, Chris
Abstract : Background: Whilst current diagnostic criteria for primary progressive aphasia syndromes (PPA) emphasise impaired language output and linguistic processing, deficits of auditory analysis are increasingly rec- ognised in PPA syndromes. We assessed phonemic discrimination and its neuroanatomical correlates in patients representing all major PPA variants, compared with typical Alzheimer's disease (tAD) and healthy age-matched individuals. Methods: 81 patients with PPA or typical Alzheimer's disease, and 73 controls performed a phonemic minimal pair discrimination task. Neuroanatomical associations of phonemic discrimination performance across the PPA cohort were assessed using voxel-based morphometry. Results: Patients with logopoenic variant primary progressive aphasia (lvPPA) as a group performed sig- nificantly worse than both the healthy control group and other PPA variants, after adjusting for auditory verbal working memory. Patients with typical Alzheimer's disease showed a similar pattern of performance to the lvPPA group. Voxel-based morphometry revealed a significant association of regional grey matter in left angular gyrus with phonemic discrimination performance. Conclusions: Impaired phonemic discrimination is a component of lvPPA and may help differentiate this syndrome from other forms of PPA. These findings speak to the emerging theme of auditory perceptual dysfunction in the progressive aphasias, with implications both for refining diagnostic criteria and developing new clinical biomarkers. jeremy.johnson@doctors.org.uk